2017
DOI: 10.1038/s41598-017-11863-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy risk stratification of thyroid nodules: comparisons of four ultrasound Thyroid Imaging Reporting and Data Systems in surgically resected nodules

Abstract: To compare the efficiency of four different ultrasound (US) Thyroid Imaging Reporting and Data Systems (TI-RADS) in malignancy risk stratification in surgically resected thyroid nodules (TNs). The study included 547 benign TNs and 464 malignant TNs. US images of the TNs were retrospectively reviewed and categorized according to the TI-RADSs published by Horvath E et al. (TI-RADS H), Park et al. (TI-RADS P), Kwak et al. (TI-RADS K) and Russ et al. (TI-RADS R). The diagnostic performances for the four TI-RADSs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In addition, Yoon et al found that both the TI‐RADS of Kwak et al and the ATA guidelines provided effective malignancy risk stratification for thyroid nodules. In a comparative study of 6 guidelines for small thyroid nodules, Yoon et al found that the sensitivity and NPV were the highest for the TI‐RADS of Kwak et al In a comparative study of 4 TI‐RADSs in surgically resected nodules, Wang et al also found that with its higher sensitivity, the TI‐RADS of Kwak et al was convenient and practical for the management of thyroid nodules in clinical practice. The malignancy rate of each category in this study was consistent with that of Kwak et al, suggesting the universe applicability of this TI‐RADS for the Eastern Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yoon et al found that both the TI‐RADS of Kwak et al and the ATA guidelines provided effective malignancy risk stratification for thyroid nodules. In a comparative study of 6 guidelines for small thyroid nodules, Yoon et al found that the sensitivity and NPV were the highest for the TI‐RADS of Kwak et al In a comparative study of 4 TI‐RADSs in surgically resected nodules, Wang et al also found that with its higher sensitivity, the TI‐RADS of Kwak et al was convenient and practical for the management of thyroid nodules in clinical practice. The malignancy rate of each category in this study was consistent with that of Kwak et al, suggesting the universe applicability of this TI‐RADS for the Eastern Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…proposed by Kwak et al (Kwak TIRADS) has been proven to be practical and easily applicable in the assessment of thyroid nodules 8,[13][14][15][16][17][18][19][20] , and can be performed by simply counting the number of suspicious US features without considering the malignancy probability of each US feature. One recent study compared the diagnostic efficiency of Kwak and ACR TIRADS and found the former to have higher AUC and accuracy 19 .…”
mentioning
confidence: 99%
“…A patient's nodule is classified by comparing it with this set of standard nodules. This process is difficult to integrate into clinical routine and does not cover all types of thyroid nodules (14,15). More recently, several further TIRADS versions were introduced, including the Korean-TIRADS (16)(17)(18), based on the modified publication by Kwak et al in 2011 and 2013 (19,20).…”
mentioning
confidence: 99%
“…Basically, in the Kwak-TIRADS a sum score for each thyroid nodule according to 5 defined sonographic nodule features is calculated to determine the need for fine-needle biopsy. This simple scoring system is more applicable to the classification of thyroid nodules in a clinical setting (14,15,18). The American College of Radiology presented a more sophisticated TIRADS in 2015 (21,22), and the EU-TIRADS by the European Thyroid Association followed in 2017 (23).…”
mentioning
confidence: 99%